2008
DOI: 10.3748/wjg.14.1805
|View full text |Cite
|
Sign up to set email alerts
|

Intragastric injection of botulinum toxin for the treatment of obesity. Where are we?

Abstract: Obesity has reached epidemic proportions particularly in western countries. Most non-surgical treatments of this condition are disappointing. Since 2005, several studies evaluating the effect of Botulinum Toxin type A (BT-A) in gastric antrum by means of endoscopy for the treatment of obesity have been published. This treatment modality was based on the observation that gastric injection of BT-A in laparatomized rats induced a significant reduction of food intake and body weight. Nowadays, 6 studies have been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 35 publications
0
16
0
Order By: Relevance
“…Tolerance (Table VIII) All documented series coincide in stating that it is safe, well tolerated treatment without significant side effects, both gastric and neuromuscular (71), regardless of dose and gastric place of BTA administration (62,64,(66)(67)(68)72).…”
Section: Techniquementioning
confidence: 98%
“…Tolerance (Table VIII) All documented series coincide in stating that it is safe, well tolerated treatment without significant side effects, both gastric and neuromuscular (71), regardless of dose and gastric place of BTA administration (62,64,(66)(67)(68)72).…”
Section: Techniquementioning
confidence: 98%
“…In one study (64), the toxin was injected both into the antrum and the gastric fundus. In the other studies, it was only injected in the antrum, which likely explains the differences in results that were observed (66). Additional studies are needed to assess the role of botulium toxin in the treatment of obesity.…”
Section: Botulinum Toxinmentioning
confidence: 98%
“…A study published two years later (60) showed that intragastric injection of botulinum toxin was safe and well tolerated. The published studies (60)(61)(62)(63)(64)(65)(66), however, have reported conflicting results. One study performed by an Italian group (64) reported a delay in gastric emptying, early satiety and body weight reduction.…”
Section: Botulinum Toxinmentioning
confidence: 99%
“…Subsequently, similar findings were confirmed by Coskun et al in obese rats [13]. In humans, injections with BoNT-A has led to conflicting results, probably coming from differences in the sites of administration (antrum and/or fundus region), the doses of the toxin, and patient selection [14]. Very recently, in a meta-analysis and meta-regression of eight studies, Bang et al analyzed a total of 115 patients (79 treated vs. 36 placebo).…”
Section: Introductionmentioning
confidence: 68%